אם g (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1}, מה זה g (3)?

אם g (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1}, מה זה g (3)?
Anonim

תשובה:

#g (3) = 6 #

הסבר:

רק תחליף 3 בכל מקום שיש #איקס#

# 3 (3) = שורש (3) (3 ^ 2-1) + 2sqrt (3 + 1) #

#g (3) = root (3) 8 + 2sqrt4 #

#g (3) = 2 + 2sqrt4 #

#g (3) = 2 + 2xx2 #

#g (3) = 2 + 4 #

#g (3) = 6 #

תשובה:

#g (3) = 6 #

הסבר:

תקע #3# in #איקס#

#g (3) = root3 (3 ^ 2-1) + 2sqrt (3 + 1) #

לפשט

#g (3) = root3 (9-1) + 2sqrt (4) #

#g (3) = root3 (8) + 2sqrt (4) #

#g (3) = 2 + 2 (2) #

#g (3) = 2 + 4 #

#g (3) = 6 #